Boosting travel agency efficiency: A holistic approach - Febrian, Wenny Desty (Goodwood Publishing, 2025)
Purpose: This study examines the influence of Green Human Resource Management (GHRM) and Human Resource Information Technology (HRIT) on productivity and organizational culture in travel bureaus, including their direct and indirect effects. Research Methodology: This study adopts a quantitative approach using survey data from travel bureau employees. Analysis is conducted with Structural Equation Modeling (SEM) using structured questionnaires and statistical software to test hypotheses. Results: GHRM and HRIT positively influence productivity but do not significantly impact organizational culture. Productivity positively influences organizational culture, while GHRM and HRIT have no significant indirect effects on it through productivity. Conclusions: GHRM and HRIT enhance productivity in travel bureaus but do not influence organizational culture. However, productivity significantly impacts organizational culture, fostering a positive work environment. Limitations: This study is limited to travel bureaus, restricting generalizability. Self-reported data may introduce bias, and its cross-sectional design prevents long-term causal inferences. Contribution: This study expands the literature on GHRM, HRIT, and organizational performance in travel bureaus, offering practical insights for boosting productivity. It also emphasizes the need for further research on factors shaping organizational culture.